2022
DOI: 10.17509/ije.v15i1.46153
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Generation Z Teachers’ Work Values: Implications to Educational Leadership and Management

Ariel C. Venida

Abstract: Being a leader or a manager in today’s organizations has become even more challenging due to increased workplace generational diversity. Gen Z teachers belong to the newest generation who have officially joined the workforce, making schools home to four different generations with unique work values. As more generations of teachers enter the workforce, one-size-fits-all management and leadership style becomes no longer applicable. Therefore, it becomes imperative for the school leaders and managers to better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Focus more on retirement time so you don't think about doing productive things. In contrast to Gen Y, the results showed that leadership style has a positive effect on job performance, which is in line with research by Steinmann et al (2018), Venida (2022), andHasmin et al (2022) who suggests that leadership is the application of various behaviors and methods, leading members to achieve common goals. Throughout this process, leaders interact with members and influence each other to complete tasks and achieve goals.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Focus more on retirement time so you don't think about doing productive things. In contrast to Gen Y, the results showed that leadership style has a positive effect on job performance, which is in line with research by Steinmann et al (2018), Venida (2022), andHasmin et al (2022) who suggests that leadership is the application of various behaviors and methods, leading members to achieve common goals. Throughout this process, leaders interact with members and influence each other to complete tasks and achieve goals.…”
Section: Discussionsupporting
confidence: 87%
“…Research from Venida (2022) obtained the results that work values influence performance, work attitude also influences performance, and generational differences moderate the relationship between work values and performance. However, several research results are inversely proportional to the benefits arising from generational factors having different work values (Cennamo & Gardner, 2008;Haryokusumo & Wibowo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects an inclusive and collaborative work culture among SMK teachers in Gunung Kidul. Additionally, most respondents also reported a positive attitude towards teamwork, indicating that they have a constructive work orientation and support each other in team collaboration Venida (2022). suggests that improving teachers' commitment to the organization can be accomplished by strengthening teamwork, implementing effective situational leadership by the principal, and nurturing strong self-efficacy among teachers.…”
mentioning
confidence: 94%